Different Placement Practices for Different Families? Children’s Adjustment in LGH Adoptive Families - Costa, Pedro Alexandre; Tasker, Fiona; Leal, Isabel Pereira (Frontiers in Psychology, 2021)
Objective: The purpose of this study was to examine the characteristics of children placed with lesbian, gay, and heterosexual adopters, and to examine children’s problem behaviors and positive psychosocial adjustment across the three family types. Background: Children adopted from care face greater developmental difficulties than children raised by their birth families, although adoptive parents may buffer the negative effects of early adversity on their children’s psychosocial adjustment. In addition, there is evidence that children with hard-to-place profiles may be more likely to be matched with lesbian and gay parents. Method: A final sample of 149 adoptive families from across the United Kingdom was recruited: 71 heterosexual parented, 39 lesbian parented, and 39 gay parented. Results: The results showed that gay and lesbian parents were more likely than heterosexual parents to be matched with hard-to-place children, partially because they were more open to being matched with children with hard-to-place profiles. However, no differences among the three family types on children’s psychosocial adjustment were found, when controlling for children’s early adversity. Conclusion: Adopted children displayed similar levels of problem behaviors and positive adjustment in lesbian, gay, and heterosexual parented families. Early adversity and having a physical problem/disability accounted for much of the variance in problem behaviors whereas parenting did not. In contrast, it was suggested that parenting processes, namely, parental closeness, may help to explain children’s positive adjustment.